Top Gun, Maverick : music from the motion picture [compact disc] - Balfe, Lorne; Faltermeyer, Harold; Lady Gaga; Zimmer, Hans (Interscope, 2022)
After several delays, the sequel to Top Gun is flying into theaters. The soundtrack includes the new Lady Gaga single Hold My Hand as well as OneRepublic's I Ain't Worried, and the Kenny Loggins classic Danger Zone.